2015
DOI: 10.1038/srep08506
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Folic Acid Supplementation and the Risk of Congenital Heart Defects in Offspring: A Meta-Analysis of Epidemiological Observational Studies

Abstract: Epidemiological studies have reported conflicting results regarding the association between maternal folic acid supplementation and the risk of congenital heart defects (CHDs). However, a meta-analysis of the association between maternal folic acid supplementation and CHDs in offspring has not been conducted. We searched the MEDLINE and EMBASE databases for articles cataloged between their inceptions and October 10, 2014 and identified relevant published studies that assessed the association between maternal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 46 publications
3
71
2
2
Order By: Relevance
“…Our findings supported the previous studies by Hernandez-Diaz et al (17) and Czeizel et al (18), which consistently demonstrated that maternal exposure to trimethoprimsulfonamide treatment during the first trimester was associated with 2-3-folds of the risk of CHD. It has been suggested that trimethoprim-sulfonamide as folate antagonists works by inhibiting dihydrofolate reductase, with a similar mode of action to that of the recognized teratogenic drug methotrexate, is suspected of inducing malformations when given during the critical period (19,20). Maternal self-reported exposure to trimethoprim-sulfonamide is very low in this study (only two in cases and zero in controls), and a couple of mothers did not report or remember the exact name of the antibiotics.…”
Section: Discussionmentioning
confidence: 83%
“…Our findings supported the previous studies by Hernandez-Diaz et al (17) and Czeizel et al (18), which consistently demonstrated that maternal exposure to trimethoprimsulfonamide treatment during the first trimester was associated with 2-3-folds of the risk of CHD. It has been suggested that trimethoprim-sulfonamide as folate antagonists works by inhibiting dihydrofolate reductase, with a similar mode of action to that of the recognized teratogenic drug methotrexate, is suspected of inducing malformations when given during the critical period (19,20). Maternal self-reported exposure to trimethoprim-sulfonamide is very low in this study (only two in cases and zero in controls), and a couple of mothers did not report or remember the exact name of the antibiotics.…”
Section: Discussionmentioning
confidence: 83%
“…54 A meta-analysis of the association between maternal folic acid supplementation and CHDs provide evidence that maternal folate supplementation is associated with a significantly decreased risk of CHDs (RR = 0.72, 95% CI: 0.63-0.82). 55 Homocysteine acts as folic acid antagonist and increased levels of maternal serum homocysteine are associated with increased risk of occurrence of CHDs in their offsprings as altered homocysteine metabolism may play role in CHDs. 56 Multivitamin use has been associated with lower risks for some birth defects.…”
Section: Folic Acid Antagoinstmentioning
confidence: 99%
“…Результаты исследований последних лет подтверждают, что прием фолиевой кислоты во время беременности снижает риск ВПС на 28-39% [30][31][32]. Была продемонстрирована Примечание.…”
Section: Introductionunclassified